Study on the Resistance of TiO2-Attapulgite Composite Coating on Concrete Surface to Freshwater Mussel Erosion - YUAN Xianfu, YANG Zongcheng, HE Xiaoyan, LIU Yuhan, BAI Xiuqin (Cailiao Baohu, 2025)
Freshwater mussels are common large fouling organisms in freshwater.They easily attach to the concrete surfaces of water-conservancy structures and damage the concrete.Coating protection is an effective method to prevent erosion by freshwater mussels.In this study，a TiO2-ATP composite coating was fabricated by air spraying after modifying epoxy resin with hydroxyl-terminated polydimethylsiloxane (H-PDMS)and loading it with titanium-dioxide (TiO2) nanoparticles and attapulgite (ATP) microparticles.A 30 d freshwater mussel erosion test was conducted，and the protective performance of the coating was evaluated by environmental scanning electron microscopy，thermogravimetric analysis， high-performance automatic mercury porosimetry and an electronic universal testing machine.Results showed that the surface contact angle of the TiO2-ATP composite coating reached 138.7°±1.6°.The water-absorption ratios of concrete specimens protected by the coating were recorded as 0.08%and 0.13%after 24 h and 48 h immersion， respectively.After 30 d of erosion， the coated specimens suffered a mass loss of 3.71%， exhibited a porosity of 10.21%， and displayed a compressive strength 22.76%higher than that of uncoated specimens.These findings demonstrated that the TiO2-ATP composite coating effectively delayed calcium leaching from concrete， prevented erosion by freshwater mussel byssus， reduced water penetration， and markedly enhanced the durability of the concrete structure.